The rights of nature and the human right to nature: an overview of the European legal system and challenges for the ecological transition - Alves, Fátima; Costa, Paulo Manuel; Novelli, Luca; Vidal, Diogo Guedes (Frontiers in Environmental Science, 2023)
Introduction: The recognition of the Rights of Nature has been established though several constitutional, legislative, and judicial enactments, which aim to provide legal protection for non-humans’ entities and natural systems. Although some countries have made progress in recognizing the rights of nature, the prevailing assumption remains that nature is a resource to be exploited for human benefit. In the context of ecological transition debates, it is important to understand how the European legal system perceives Nature and its rights. Achieving a significant shift in legal and cultural norms that prioritize nature’s protection may be challenging. Methods: This paper reports on research conducted in a sample of 6 countries within the PHOENIX consortium, a European H2020 project that aims to develop participatory methodologies and democratic innovations to facilitate the ecological transition as envisioned by the European Green Deal, whose objective was to find out how these countries embodied the Rights of nature into their legal systems, both at constitutional level and at the level of environmental and related laws and policies. Results: The results indicate that in legislative terms, concepts of nature are absent, and instead, the term environment or natural resources are used. Furthermore, rights of nature are rarely recognized in all countries, with anthropocentric and in instrumental views prevailing. In contrast, the human right to Nature is widely recognized in all countries, referring to the right of all individuals to access to and live in a healthy environment. Discussion: Despite the importance of the human right to Nature as a matter of equity and justice, failure to recognise the rights of nature and protect/respect its limits may constitute a potential barrier to ecological transition.